Sandflies (Diptera, Psychodidae) from forest areas in Botucatu municipality, central western Sao Paulo State, Brazil - Cutolo, Andre Antonio; Bianchi Galati, Eunice Aparecida; Von Zuben, Claudio José [UNESP] (Biomed Central Ltd., 2013)
Background: The study of the distribution and ecology of sandfly species is essential for epidemiological surveillance and estimation of the transmission risk of Leishmania spp. infection.Findings: In the present study, sandflies were captured in native fragmented forest areas in Rubiao Junior district, Botucatu municipality, Sao Paulo state, Brazil, between September 2001 and January 2005. A minimum of two automatic light traps were installed per night from 6 pm to 8 am, in different months, resulting in approximately 900 collecting hours. During this period, 216 sandfly specimens of sixteen species were captured. Pintomyia monticola and Brumptomyia guimaraesi were the most abundant with 56 specimens (25.93%) captured per species, followed by Pintomyia fischeri 28 (12.96%) and Psathyromyia pascalei 18 (8.33%). Other captured species were Lutzomyia amarali, Sciopemyia sordellii, Psathyromyia aragaoi, Nyssomyia whitmani, Migonemyia migonei, Pintomyia bianchigalatiae, Pintomyia misionensis, Brumptomyia carvalheiroi, Brumptomyia cardosoi, Brumptomyia cunhai, Brumptomyia nitzulescui, Brumptomyia brumpti and Brumptomyia spp. represented by 58 (26.85%) specimens.Conclusions: Although less frequently found, the presence of Pintomyia fischeri, Nyssomyia whitmani and Migonemyia migonei, known vectors of Leishmania braziliensis, indicates risk of American cutaneous leishmaniasis occurrence. Moreover, the absence of Lutzomyia longipalpis-the main vector of Leishmania infantum chagasi, which is the agent of American visceral leishmaniasis-suggests that there is no risk of introduction and establishment of this disease in the studied area.
Keywords: Cutaneous leishmaniasis; Vector; Sandfly; Brazilian savannah; Semideciduous forest; Cuesta